Electro-oxidation of wastewater from a beauty salon: The influence of electrolyte type in the removal of organic load and energy consumption - Vieira, Gleilson de F.; Barbosa Segundo, Inalmar D.; Santos, José Eudes L.; Gondim, Amanda D.; dos Santos, Elisama V. [UNESP]; Martínez-Huitle, Carlos A. [UNESP] (Elsevier, 2023)
The aim to ensure water quality and wastewater treatment is sought by the United Nations and expressly proposed in the sixth sustainable development goal (SDG6). As universally available services, beauty salons (BS) are places that deal with potentially hazardous chemicals, and their effluent should be treated before goes to the sewage system. This work presents a wide characterization of a BS effluent and its respective electrochemical treatment by using boron-doped diamond (BDD) as the anode, stainless steel as the cathode, as well as NaCl and Na2SO4 as additional supporting electrolytes. The effectiveness of the processes and the comparative study of the performance of the electrolytes were mainly performed by the analysis of chemical oxygen demand (COD) removal and energy consumption. However, other parameters were taken into consideration, such as color, conductivity/salinity, pH, and more extensive analysis regarding the cause of turbidity and the appearance of a precipitate before and during the electrolysis. NaCl proved to be more efficient than Na2SO4 to treat this BS effluent; it was not only because achieves a better COD removal (70% against 64%, with a current density of 10 mA cm−2), but also because it promoted an effluent with less turbidity and color, besides a pH closer to neutral, with no need to further correction before discharge. Regarding the electrolyte concentration, the excess of salt proved to be necessary to promote a higher removal rate in COD values with less charge and energy consumption. Thus, the concentration of 0.16 M of NaCl associated with a current density of 10 mA cm−2 was chosen as the best condition for treating this effluent. In addition, Si-based oxides were detected in the raw effluent and these were pointed out as responsible for its high turbidity. Proper discharge of it into the sewage system is reached with NaCl as the electrolyte. The treatment proposed in this work deals with SDG6 and can be used as an alternative to decision-makers and governments to help in the implementation of better politics of water sanitation.
Keywords: Beauty salon effluent; diamond electrode; Electro-oxidation; High-turbidity wastewater; Precipitates analysis; Silicates